Coherent interferometry migration for hard rock diamond drill-bit seismic - Sun, Bai Chun; Bóna, Andrej; Zhou, B.; King, A. (SEG, 2014)
We use the direct wave interferometry migration with coherency measurement to image the diamond drill-bit. The success of such imaging can prove if the direct waves from the drill-bit can be detected. The drilling signals usually contain strong narrow band interference noises. We suggest to use interferometry by deconvolution for migration, which widens the cross spectrum, hence the weak coherent features can be better observed. Additionally, we suggest to integrate coherent measurement of semblance or Multiple Signal Classification (MUSIC) into the algorithm in order to detect weak drill-bit signal. We test both methods with a synthetic and a diamond drill-bit seismic-while-drilling (SWD) field data. MUSIC coherency shows relatively better spatial resolution in contrast to semblance method. It also demonstrates better detectability of weak signal than summation and semblance. Our field SWD data also indicates that the interferometry migration can image the diamond drill-bit with appropriate survey parameters, and the MUSIC method achieves a high spatial resolution.